Home Industri Sebagai Pemberdayaan Perempuan dalam Meningkatkan Ekonomi Keluarga di Bandar Selamat Kecamatan Medan Tembung - Khairunnisa Khairunnisa; Vina Aulia; Ramadhan Fitriani; Tumiar Sidauruk (Journal on Education, 2024)
This research aims to assess efforts to increase women's participation through home industry activities to improve economic welfare in Bandar Selamat, Medan Tembung District. It is noted that women's role in the family economy is often minimal and often depends on the husband's income. Based on Moser's empowerment theory, as quoted by Bogong Suyanto and Emy Susanti, women's empowerment is not about dominating men, but about increasing women's independence and internal strength. This research question covers the factors underlying women's empowerment in Bandar Selamat and the steps women take to improve the family economy. This research aims to identify these factors and evaluate the efforts made by women in the context of improving family economic welfare.